2016
DOI: 10.1002/chem.201600708
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Efficient Oxidative Cycloreversion Reaction of a π‐Extended Photochromic Terarylene

Abstract: We report herein a dramatic improvement in the kinetics and efficiency of an oxidative cycloreversion reaction of photochromic dithiazolylthiazoles. The cycloreversion reaction of a colored isomer of dithiazolylthiazole proceeds not only by photo-irradiation, but also through chemical oxidation with a net efficiency far exceeding 100 % owing to a chain reaction mechanism. By introducing aromatic groups on the reactive carbon atoms at the ends of a photoreactive 6π system in a dithiazolylthiazole, the net bleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…[80] The charge transfer between surface and molecules is also important in the context of bistable compounds because the properties of the o and c forms in their charged radical states are different from their neutral ones. [28][29][30][31][32][33][34][35][36] Kim's group clearly demonstrated this when they showed that the c form is more stable than the o form in STM studies of 15 (Figure 7a) on metallic surfaces. Deposition and subsequent imaging of the assynthesized o forms resulted in the observation of both o and c forms, seen as extended and triangular lobes respectively, on Cu(111) at room temperature (Figure 7b).…”
Section: Diarylethenes Under Uhvmentioning
confidence: 91%
See 3 more Smart Citations
“…[80] The charge transfer between surface and molecules is also important in the context of bistable compounds because the properties of the o and c forms in their charged radical states are different from their neutral ones. [28][29][30][31][32][33][34][35][36] Kim's group clearly demonstrated this when they showed that the c form is more stable than the o form in STM studies of 15 (Figure 7a) on metallic surfaces. Deposition and subsequent imaging of the assynthesized o forms resulted in the observation of both o and c forms, seen as extended and triangular lobes respectively, on Cu(111) at room temperature (Figure 7b).…”
Section: Diarylethenes Under Uhvmentioning
confidence: 91%
“…The charge transfer between surface and molecules is also important in the context of bistable compounds because the properties of the o and c forms in their charged radical states are different from their neutral ones . Kim's group clearly demonstrated this when they showed that the c form is more stable than the o form in STM studies of 15 (Figure a) on metallic surfaces.…”
Section: Stm Of Diarylethenesmentioning
confidence: 99%
See 2 more Smart Citations
“…The downfield shifts of these methylp rotons after the photoinduced elimination (Supporting Information, Figures S12, S13) suggested that the ring-current effect of 2-phenylthiazole unit operated on these methyl groups in PAGs 1 and 2.O nt he other hand, bulky substituents on the reactive carbon atoms as aromatic leaving groups markedly decrease the efficiency of electrocyclization reaction for PAGs 3 and 4. [40] In addition for PAG-5,t he S···N interaction operatingb etween the central and the side thiazolyl units, [33] the CH···N interaction between the central thiazole and the side benzo[b]thiophene unit may contribute to the stabilization of photoreactive conformer.B ecause of the hydrogen-bonding nature of CH···N interaction, the f acid value is expectedt os ignificantly drop in protic and polar solvents (0.23 in methanol).…”
Section: Photoirradiation Of Pre-pag-5 and Pag-5mentioning
confidence: 99%